2021
DOI: 10.3390/cells10030539
|View full text |Cite
|
Sign up to set email alerts
|

KLF4, Slug and EMT in Head and Neck Squamous Cell Carcinoma

Abstract: Epithelial to mesenchymal transition (EMT) is clinically relevant in head and neck squamous cell carcinoma (HNSCC). We hypothesized that EMT-transcription factors (EMT-TFs) and an anti-EMT factor, Krüppel-like-factor-4 (KLF4) regulate EMT in HNSCC. Ten control mucosa and 37 HNSCC tissue samples and three HNSCC cell lines were included for investigation of EMT-TFs, KLF4 and vimentin at mRNA and protein levels. Slug gene expression was significantly higher, whereas, KLF4 gene expression was significantly lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…6 and Fig. S7), which is in accordance with reports from others [34][35][36]. A recent meta-analysis of the prognostic value of EMT-TFs in HNSCC disclosed that Twist, Snail, SLUG, and Zeb1 correlated with significantly poorer OS [37].…”
Section: Discussionsupporting
confidence: 90%
“…6 and Fig. S7), which is in accordance with reports from others [34][35][36]. A recent meta-analysis of the prognostic value of EMT-TFs in HNSCC disclosed that Twist, Snail, SLUG, and Zeb1 correlated with significantly poorer OS [37].…”
Section: Discussionsupporting
confidence: 90%
“…Low expression of p53 together with low expression of E-cadherin may act as an independent unfavorable prognostic sign in oral squamous cell carcinoma ( Fan et al, 2013 ). For head and neck cancer cells, it was shown that the negative status of p53 contributed to increased Slug expression ( Ingruber et al, 2021 ). The p53 and Slug interaction was also noted for the embryonic development.…”
Section: P53 and Emt-tfsmentioning
confidence: 99%
“…GAPDH was used as a housekeeping gene, and relative quantities of the transcripts were calculated by pairwise differences of threshold cycles (δCT) of the gene of interest and the loading control housekeeping gene 30 . For the final analysis, we used the relative quantification and related the PCR signal in the cells to a control reference gene expression level 12 . The identity of the PCR products of genes was confirmed by Sanger sequencing by Microsynth Austria (Vienna, Austria) 12 .…”
Section: Methodsmentioning
confidence: 99%
“…These traits are also characteristic of epithelial to mesenchymal transition (EMT) 8 10 , a complex, variable, and context-specific cellular program that enables carcinoma cells to suppress epithelial characteristics in favour of mesenchymal differentiation 11 . In cancer, EMT is usually incomplete and reversible, resulting in coexpression of epithelial and mesenchymal markers 12 . EMT-associated reprogramming is regulated by various transcription factors, including SNAI1, SNAI2, ZEB, and TWIST 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation